Halfway to sustainability: Management lessons from community-based, marine no-take zones in the Mexican Caribbean. (July 2018) - Ayer, Austin; Fulton, Stuart; Caamal-Madrigal, Jacobo Alejandro; Espinoza-Tenorio, Alejandro
Abstract: Spatial closure regimes such as marine protected areas (MPAs) have emerged as a prominent tool in the effort to balance ecosystem health and fishery productivity. As MPAs have proliferated, the conservation community has begun to supplement traditional biological metrics with social and community considerations in the way it seeks to manage and evaluate such tools. To assess management outcomes and opportunities for a network of community-based, marine no-take zones (NTZs) in the Mexican Caribbean, semi-structured interviews were carried out with fishers and key management stakeholders. Findings indicate that the community-based management strategy has inherent tradeoffs between community engagement and conservation potential. Managers have succeeded in fostering high levels of community support for the initiative, but significant challenges remain, most notably the high presence of illegal fishing within NTZs. Successes and challenges of the community-based management strategy are documented and evaluated within a fisheries resource management framework. As the NTZ network undergoes legal renovation following the completion of its initial five-year term, this work serves as an important resource for both reflection on, and adaptation of, the community-based NTZ management regime. Highlights: Community-based NTZs in Mexican Caribbean enjoy positive fisher perceptions. Community-based management has inherent tradeoffs between engagement and efficacy. Uncoordinated governance context hinders NTZ enforcement and challenges sustainability. Heuristic fisheries resource management model facilitates improved NTZ management.